Hepatitis B‐related stigma among Chinese immigrants living with hepatitis B virus in Australia: A qualitative study. (6th September 2022) - Jin, Defeng; Brener, Loren; Treloar, Carla
Abstract: Chinese immigrants in Australia are overrepresented among people with chronic hepatitis B virus (PWCHB) but experience poor access to healthcare. Given the historical discriminatory policies against PWCHB in mainland China, this study aimed to explore the lived experiences of stigma and discrimination surrounding hepatitis B virus (HBV) among Chinese immigrants originally from mainland China. Semi‐structured in‐depth interviews were conducted by a researcher with a Chinese background in 2019–2020. Sixteen Chinese immigrants living with HBV were recruited across Sydney and Melbourne through advocacy and support groups. This study is positioned in social constructionism. Data analysis was informed by the Health Stigma and Discrimination Framework that highlights the interaction between layered stigmas. This study revealed the historical, social and cultural construction of HBV‐related stigma among PWCHB and demonstrated how this stigma was manifested across socioecological levels in China and Australia. Findings show that HBV‐related stigma has mostly been driven by knowledge deficits about HBV and fear of HBV infection. HBV‐related stigma was mostly demonstrated around social isolation including isolation imposed by family and the community and employment restrictions in the Chinese workplace. In the Australian context, HBV‐related stigma was related to the ethnic and cultural background of PWCHB, and primarily occurred as anticipated stigma in the community and in employment. The findings provide significant insights for crosscutting research and policy endeavours to develop and test cross‐disciplinary initiatives that more broadly address the complex lived realities of Chinese immigrants living with hepatitis B virus.